1991
DOI: 10.3382/ps.0702460
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein Concentration, Amino Acid Supplementation, and Daily Time of Access to High- or Low-Protein Diets on Egg Weight and Components in Laying Hens

Abstract: Feeding a 13% CP diet based on corn and soybean meal and supplemented with methionine to laying hens results in reduced egg weight in comparison with hens fed a corn and soybean meal methionine-supplemented diet containing 16% CP. An experiment was conducted to determine whether the egg weight reduction could be eliminated by supplementing the low-protein diet with additional lysine, methionine, and tryptophan or by adding glycine and glutamic acid to increase the amino nitrogen to a level equivalent to 16% CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 3 publications
3
33
0
4
Order By: Relevance
“…According to Carey et al (1991b), Shafer et al (1996) and Shafer et al (1998), egg component weight (g/egg) was increased by increasing methionine intake levels from 326 to 556 mg/hen/day, while TSAA or methionine had no effect on albumen or yolk percentages, and ratio of yolk: albumen (Carey et al, 1991b;Hussein and Harms, 1994;Novak et al, 2004). Based on our study, the results indicated that the decrease in egg weight in the basal diet group might come from decreases in both yolk and albumen that is agreed with report by Romanoff and Romanoff (1949), but not with report by Penz and Jensen (1991) in which decrease of egg size was mainly resulted from decrease of egg albumen. Under heat stress conditions, increment of yolk (%) and reduction of albumen (%) were observed in hens fed lowprotein diet (14% CP with 0.26% methionine) (Bunchasak and Silapasorn, 2005).…”
Section: Egg Component and Internal Egg Qualitysupporting
confidence: 82%
See 1 more Smart Citation
“…According to Carey et al (1991b), Shafer et al (1996) and Shafer et al (1998), egg component weight (g/egg) was increased by increasing methionine intake levels from 326 to 556 mg/hen/day, while TSAA or methionine had no effect on albumen or yolk percentages, and ratio of yolk: albumen (Carey et al, 1991b;Hussein and Harms, 1994;Novak et al, 2004). Based on our study, the results indicated that the decrease in egg weight in the basal diet group might come from decreases in both yolk and albumen that is agreed with report by Romanoff and Romanoff (1949), but not with report by Penz and Jensen (1991) in which decrease of egg size was mainly resulted from decrease of egg albumen. Under heat stress conditions, increment of yolk (%) and reduction of albumen (%) were observed in hens fed lowprotein diet (14% CP with 0.26% methionine) (Bunchasak and Silapasorn, 2005).…”
Section: Egg Component and Internal Egg Qualitysupporting
confidence: 82%
“…Two types of imbalance may be recognized that caused by the addition of a relatively small quantity of an amino acid to a low protein diet, and by an incomplete mixing of amino acids (D' Mello, 1994). Although Shafer et al (1996), Chung et al (1998) and Novak et al (2004) reported that dietary methionine directly improved feed intake, egg weight, egg mass and FCR, but Penz and Jensen (1991), Keshavarz and Jackson (1992) and Summers et al (1988) reported that methionine supplement in normal or low protein diets usually do not depress feed intake and egg size of hens. The results in our current study still suggested that insufficiency of methionine intake emphasize to depress egg production performance via reduction of feed intake due to amino acids imbalance.…”
Section: Egg Production Performancementioning
confidence: 99%
“…Penz and Jensen (1991), despite providing experimental diets with sufficient levels to meet 120% of Met, Lys and Trp requirements for hens, found that low-protein diets (13% CP) resulted in laying hens with higher feed conversion than the birds that received the control diet (13% CP).…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have been successful in reducing N excretion by reducing the crude protein (CP) content in the diet with and without supplemental amino acids (Schutte et al, 1992;Summers, 1993;Jamroz et al, 1996;Blair et al, 1999) but with mixed effects on production variables. Penz and Jensen (1991) reported decreased egg weight, body weight (BW), albumen, and yolk percentage, and poorer feed conversion in Dekalb XL hens from 28 to 34 weeks of age when fed lowprotein diets (13% protein) supplemented with Lys, Met, or Trp individually or in combination at a level of 20% above the NRC recommendations (NCR, 1984) and a low-protein diet supplemented with amino N supplying amino acids (Gly and Glu) to equal the 16% protein diet in total N. Keshavarz and Jackson (1992) fed a lowprotein diet supplemented with amino acids. Performance was equivalent to a positive control in some, but not all, performance traits.…”
Section: Introductionmentioning
confidence: 99%